Fases de diagnóstico, diseño y entrega de la estructura organizacional para las áreas de compras y suministros y de talento humano en una empresa del sector minero (2022)
This degree project is carried out in different phases, those phases are: Diagnosis, design and delivery of the organizational structure for the areas of purchases and supplies and human resources in a company in the mining sector. The planning and execution of this work is executed under the methodologies taught throughout the specialization and its main base is the cascade methodology with small sections of agile methodologies on specific issues of feedback and lessons learned. Based on what was taught in the specialization, planning is made based on areas of knowledge and processes to create a baseline for the project, which will be the starting point for its execution, control, and closure. All the documentation generated in the development of this degree project was delivered to the company that had the role of client and whose manager is the sponsor, these documents were validated in conjunction with the company.